Temporal and spatial patterns of defecation in wild boar - Francesco Ferretti; Kate Storer; Julia Coats; Giovanna Massei (Wildlife Society Bulletin)
ABSTRACT Worldwide, wild boar (Sus scrofa) and feral pigs are involved in environmental damage and disease transmission. These impacts are often associated with relatively high local densities of pigs, so the monitoring of population trends is important. Dung counts can be used to estimate population trends, but knowledge of daily defecation rates (DDRs) is needed to estimate absolute numbers. To address this issue, we calculated the DDRs of 18 captive, adult wild boar in July 2005 and November 2007. The mean DDR was 3.8–4.3 dung/boar/day, depending on the trial. We discuss the results by comparing the DDR of wild boar to that of other ungulates and omnivores, and we consider the implications of these results for estimating feral pig and wild boar density through dung counts. © 2014 The Wildlife Society.